Failure to Launch: One-Person-One-Fare Airline Policy and the Drawbacks to the Disabled-By-Obesity Legal Argument. Issue 2 (4th May 2021) - Rinaldi, Jen; Rice, Carla; Lind, Emily
ABSTRACT: Since January 2009, the Canadian Transportation Agency has required domestic airlines to uphold a one-person-one-fare policy (1P1F), according to which passengers requiring additional seating due to disability – including persons found to be functionally disabled by obesity – are entitled to it without extra cost. In this article, the authors show that the jurisprudence that upholds 1P1F by design makes possible domestic airline policy and practice that impose undue obstacles for, and offend the dignity of, fat persons. Specifically, because fat flyers must prove their condition is disabling, the medical documentation they must submit discursively pathologizes their bodies. Further, the process travelers must undergo to complete and submit documentation in order to qualify for the 1P1F accommodation perpetuates, even exacerbates, their vulnerability to discriminatory treatment. The authors ultimately show that policies and processes developed to comply with Canada's 1P1F standard do pathologizing and stigmatizing work because airlines have an economic interest in holding to the "disabled by obesity" model rather than adjusting the normative geographies they produce (and profit from) on flights.